The impact of firm performance on the business transfer mode - Rosemarie Kay; André Pahnke; Susanne Schlepphorst (Institut für Mittelstandsforschung (IfM) Bonn, 2018)
This paper analyzes the impact of family firms' past and future economic viability on the incumbents' decision on the business transfer mode. Using the German IAB Establishment Panel and estimating logistic regression models we show that the decision on the business transfer mode rather depends on the expected future performance than on the past one. Moreover, family businesses that are exclusively managed by their owners are more likely to be planning an intra-family succession. However, ambiguity about the future performance overrides the original intention and induces the incumbents to sell the business.
Keywords: L25; L26; M2; 330; family businesses; business succession; transfer mode; performance